2015
DOI: 10.1097/rlu.0000000000000738
|View full text |Cite
|
Sign up to set email alerts
|

Human Biodistribution and Radiation Dosimetry of S-11C-Methyl-L-Cysteine Using Whole-Body PET

Abstract: The potential radiation risks associated with C-MCYS PET imaging are within accepted limits. C-MCYS is a safe amino acid PET tracer for tumor imaging and can be used in further clinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 13 publications
2
8
0
Order By: Relevance
“…While a full range of timepoints across the whole body were not collected in this study, our calculated value is comparable to other reported effective doses for 11 C-labeled PET tracers (52,(54)(55)(56)(57). This effective dose is similar to those reported for other 11 C-labeled amino acid radiopharmaceuticals (52,54,55) and a magnitude lower than dose estimates for 18 F-labeled radiopharmaceuticals found in the literature (50,(58)(59)(60)(61)(62) due mainly to the short half-life of carbon-11.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…While a full range of timepoints across the whole body were not collected in this study, our calculated value is comparable to other reported effective doses for 11 C-labeled PET tracers (52,(54)(55)(56)(57). This effective dose is similar to those reported for other 11 C-labeled amino acid radiopharmaceuticals (52,54,55) and a magnitude lower than dose estimates for 18 F-labeled radiopharmaceuticals found in the literature (50,(58)(59)(60)(61)(62) due mainly to the short half-life of carbon-11.…”
Section: Discussionsupporting
confidence: 81%
“…While a full range of timepoints across the whole body were not collected in this study, our calculated value is comparable to other reported effective doses for 11 C-labeled PET tracers (52,(54)(55)(56)(57). This effective dose is similar to those reported for other 11 C-labeled amino acid radiopharmaceuticals (52,54,55) and a magnitude lower than dose estimates for 18 F-labeled radiopharmaceuticals found in the literature (50,(58)(59)(60)(61)(62) due mainly to the short half-life of carbon-11. This value compares well with the mean effective dose (5.9E-03 ± 2.0E-03 mSv/MBq) reported in a review of 37 dose estimates for 11 C-labeled PET tracers (56) and with the average effective dose (5.2E-03 ± 1.7E-03 mSv/MBq) from a recent review of 77 literature publications for a wide range of 11 C-labeled tracers (57).…”
Section: Discussionsupporting
confidence: 81%
“…A successful alternative is the amino acid analog O -2-[ 18 F]fluoroethyl-L-tyrosine ([ 18 F]FET) [ 4 ]. Another amino acid analog which has been proposed for the same purpose is S -[ 11 C]methyl-L-cysteine ([ 11 C]MCYS) [ 5 , 6 ]. MCYS is a naturally occurring derivative of the amino acid L-cysteine.…”
Section: Introductionmentioning
confidence: 99%
“…However, [ 11 C]MET is taken up not only by tumors but also by other inflammatory lesions, leading to low tumor specificity 30-33; additionally, it is susceptible to in vivo metabolism 34, complicating kinetic analysis. To address these deficiencies, S- [ 11 C]-methyl-L-cysteine 1L ( S -[ 11 C]CH 3 -L-CYS) and S- [ 11 C]-methyl-D-cysteine 1D ( S -[ 11 C]CH 3 -D-CYS), a pair of 11 C-labelled S -methylcysteine enantiomers ( Figure 1A and Figure S1B ), were successively developed via 11 C-isotopic substitution in our previous studies 35-38. Preliminary studies indicated that the tracers were superior to [ 18 F]FDG and [ 11 C]MET in the differentiation of tumor from inflammation 35, 36, 38-40.…”
Section: Introductionmentioning
confidence: 99%
“…To address these deficiencies, S- [ 11 C]-methyl-L-cysteine 1L ( S -[ 11 C]CH 3 -L-CYS) and S- [ 11 C]-methyl-D-cysteine 1D ( S -[ 11 C]CH 3 -D-CYS), a pair of 11 C-labelled S -methylcysteine enantiomers ( Figure 1A and Figure S1B ), were successively developed via 11 C-isotopic substitution in our previous studies 35-38. Preliminary studies indicated that the tracers were superior to [ 18 F]FDG and [ 11 C]MET in the differentiation of tumor from inflammation 35, 36, 38-40. Nevertheless, the short half-life of 11 C ( t 1/2 = 20.4 min) restricts the widespread application of these tracers, resulting in an urgent demand for 18 F-labelled SAA tracers ( 18 F, t 1/2 = 109.8 min).…”
Section: Introductionmentioning
confidence: 99%